La Tunisie: carrefour du Judaïsme antique et moderne - Allouche, Félix (Evidences, 1949)
Keywords: Judaïsme -- Djerba

A Ouargla, rites mortuaires - Germaine-Marie (Revue des Soeurs blanches, 1949)
Keywords: Coutumes -- Ouargla

La Tunisie, terre d'Islam - Rouillon, M. (Air-France revue, 1949)
Keywords: Tourisme -- Djerba

Les origines et l’habitat des Juifs en Tunisie - Donio, Elie (Bulletin Economique et Social de la Tunisie, 1949)
Keywords: Judaïsme -- Djerba

Notizia di alcuni manoscritti ibāḍiti esistenti presso l’Istituto Universitario Orientale di Napoli - Rubinacci, Roberto (Annali dell'Istituto Universitario Orientale di Napoli, 1949)
The following MSS are mentioned: Qawāʿid by Jayṭālī with glosse by Abū Sitta al-Qaṣbī; K. al-Siyar of Shammākhī; K. al-Jawāhir by Barrādī; Mukhtaṣar K. al-Khiṣāl by Abū Isḥāq Ibr. [b. Qays al-Ḥadramī]; K. al-Waḍʿ fī ‘l-Furūʿ by Jannāwunī; Qanāṭir al-Khayrāt by Jayṭālī; Mukhtaṣar by Muḥ. b. Mulūka al-Tūnisī of the same’s commentary on Durrat al-Bayḍā’ by ʿAbd al-Raḥmān al-Akhḍarī (see GAL S I, 778; S II, 706).
Keywords: Barrādī, Abū ‘l-Qāsim b. Ibrāhīm al-; Jayṭālī, Ismāʿīl b. Mūsà (13..-1350)

A Further Journey across the Empty Quarter - Thesiger, Wilfred (The Geographical Journal, 1949)
Keywords: Récits de voyage -- Oman

Note di teologia ibāḍita - Moreno, Mario (Annali dell'Istituto Universitario Orientale di Napoli, 1949)
Based on ʿAbdl. b. Ḥumayyid al-Sālimī: Bahjat al-Anwār: Sharḥ Anwār al-ʿUqūl fī ‘l-Tawḥīd. In the margin of the first volume of his K. Ṭalʿat al-Shams ʿalà ‘l-Alfiyya, Cairo n.d. Comparisons are being made with: Ism. b. Mūsà al-Jayṭālī’s Qanāṭir al-Khayrāt; Abū Yaʿqūb Yūsuf b. Ibr. al-Warjlānī’s K. al-Dalīl li-Ahl al-ʿUqūl; ʿAbd al-ʿAzīz b. Ibr. al-Muṣʿabī’s Sharḥ ʿalà ‘l-Qaṣīda al-Nūniyya al-musammāt bi’l-Nūr. Moreno researches the similarity of the Ibāḍī theological doctrines in the East and in the West, making also comparisons with the Muʿtazilites.
Keywords: Jayṭālī, Ismāʿīl b. Mūsà (13..-1350); Orientalisme -- Italie

L’Imāmato ibāḍita dell’ʿOman - Veccia Vaglieri, Laura (Annali dell'Istituto Universitario Orientale di Napoli, 1949)
La ricostituzione dell’Imamato ibāḍita nell’interno dell’ʿOmān (245); Le fonti per la storia dell’ʿOmān (247); Caratteristiche del paese (250); I principali avvenimenti anteriori alla costituzione dell’Imāmato (252); Come sorse l’Imāmato (253); L’antico Imāmato elettivo, 135-281/752-894, capitale Nezwà (256); Il periodo degli Imām sporadici (263); I Yaʿrubidi, 1034-1154/1624-1741, capitale er-Rostāq, Yabrīn, Nezwà ecc. (273); Gli Āl Bū Saʿīd o Āl Saʿīd, 1154/1741 ad oggi (278).
Keywords: Orientalisme -- Italie

Le vicende del khārigismo in epoca abbaside - Veccia Vaglieri, Laura (Rivista degli studi orientali, 1949)
Keywords: Orientalisme -- Italie

On Some Libyan ethnics in Johannis of Corippus - Lewicki, Tadeusz (Rocznik Orientalistyczny, 1949)

Djerba - Combès, Jean-Louis (Bulletin Economique et Social de la Tunisie, 1949)
Keywords: Tourisme -- Djerba

Di alcune iscrizioni in carateri latini e in lingua sconosciuta, trovate in Tripolitania - Beguinot, Francesco (Rivista degli studi orientali, 1949)
Keywords: Archéologie -- Djebel Nefousa

Due racconti in linguaggio nefusi - Cesaro, Antonio (Annali dell'Istituto Universitario Orientale di Napoli, 1949)
Keywords: Linguistique -- Djebel Nefousa

La couverture de Djerba - Borg, P. (Office Tunisien de Standardisation, 1949)
Keywords: Artisanat -- Djerba

Météorologie populaire de l’île de Djerba (Tunisie) - Dubouloz-Laffin, Marie-Louise (Nouvelle revue des traditions populaires, 1949)
Keywords: Moeurs et coutumes -- Djerba